THE FORMATION AND FUNCTIONAL VARIETIES OF THE KAZAKH OFFICIAL-BUSINESS LANGUAGE IN THE 18th-19th CENTURIES (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This article examines the formation of the Kazakh official-business language in the eighteenth and nineteenth centuries and explores the development of its functional varieties from historical-linguistic and linguostylistic perspectives. The study analyzes the linguistic characteristics of the written communication system that emerged as a result of the expanding diplomatic and administrative relations of the Kazakh steppe with the Russian Empire, the Central Asian khanates, and the internal political institutions of traditional Kazakh society. The research corpus includes official correspondence, petitions, administrative records, legal and regulatory documents, decrees, and official reports dating from the eighteenth and nineteenth centuries. Historical-comparative, descriptive, textual, and linguostylistic methods were employed to investigate the collected materials.The findings demonstrate that the Kazakh official-business language evolved into an independent functional system of written communication during the period under consideration. The analysis reveals that standardization, formulaic expression, terminological consistency, structural stability, informational precision, and emotional neutrality constituted the principal features of official texts. The study identifies and systematizes the major functional branches of the official-business language, including official correspondence, regulatory and directive documents, and administrative records. Particular attention is paid to the influence of Arabic-Persian and Russian lexical elements on the formation of the official style and the development of its terminological framework. The results contribute to a deeper understanding of the history of the Kazakh literary language, historical stylistics, and the evolution of functional styles, while also highlighting the continuity between historical official discourse and the contemporary official-business language.